Germline Copy Number Variation and Ovarian Cancer Survival - Fridley, Brooke L.; Chalise, Prabhakar; Tsai, Ya-Yu; Sun, Zhifu; Vierkant, Robert A.; Larson, Melissa C.; Cunningham, Julie M.; Iversen, Edwin S.; Fenstermacher, David; Barnholtz-Sloan, Jill; Asmann, Yan; Risch, Harvey A.; et al. (Frontiers in Genetics, 2012)
Copy number variants (CNVs) have been implicated in many complex diseases. We examined whether inherited CNVs were associated with overall survival among women with invasive epithelial ovarian cancer. Germline DNA from 1,056 cases (494 deceased, average of 3.7 years follow-up) was interrogated with the Illumina 610quad genome-wide array containing, after quality control exclusions, 581,903 single nucleotide polymorphisms (SNPs) and 17,917 CNV probes. Comprehensive analysis capitalized upon the strengths of three complementary approaches to CNV classification. First, to identify small CNVs, single markers were evaluated and, where associated with survival, consecutive markers were combined. Two chromosomal regions were associated with survival using this approach (14q31.3 rs2274736 p=1.59x10-6, p=0.001; 22q13.31 rs2285164 p=4.01x10-5, p=0.009), but were not significant after multiple testing correction. Second, to identify large CNVs, genome-wide segmentation was conducted to characterize chromosomal gains and losses, and association with survival was evaluated by segment. Four regions were associated with survival (1q21.3 loss p=0.005, 5p14.1 loss p=0.004, 9p23 loss p=0.002, and 15q22.31 gain p=0.002); however, again, after correcting for multiple testing, no regions were statistically significant, and none were in common with the single-marker approach. Finally, to evaluate associations with general amounts of copy number changes across the genome, we estimated CNV burden based on genome-wide numbers of gains and losses; no associations with survival were observed (p>0.40). Although CNVs that were not well-covered by the Illumina 610quad array merit investigation, these data suggest no association between inherited CNVs and survival after ovarian cancer.